2019
DOI: 10.1111/1462-2920.14594
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory network of Vibrio parahaemolyticus type VI secretion system 1

Abstract: Summary Type VI secretion systems (T6SSs) are widespread, tightly regulated, protein delivery apparatuses used by Gram‐negative bacteria to outcompete their neighbours. The pathogen, Vibrio parahaemolyticus , encodes two T6SSs. These T6SSs are differentially regulated by external conditions. T6SS1, an antibacterial system predominantly found in pathogenic isolates, requires warm marine‐like conditions and surface sensing for activation. The regulatory network that governs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…3). These plasmids were introduced into the surrogate platform strains, and their ability to confer T6SS1-mediated killing of a parental RIMD 2210633 prey was determined in a quantitative competition assay, as well as in a qualitative assay 43 by monitoring the survival of GFP-expressing prey. Notably, we confirmed the expression of all but one candidate E/I pair by immunoblot analysis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). These plasmids were introduced into the surrogate platform strains, and their ability to confer T6SS1-mediated killing of a parental RIMD 2210633 prey was determined in a quantitative competition assay, as well as in a qualitative assay 43 by monitoring the survival of GFP-expressing prey. Notably, we confirmed the expression of all but one candidate E/I pair by immunoblot analysis ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, the development of a surrogate T6SS platform is pivotal for the future scale up of this methodology; it allows one to screen effector candidates from any isolate that harbors the T6SS in question, even from isolates that are not amenable for genetic manipulations. Moreover, the use of our previously developed methodology 43 , in which prey survival is qualitatively assessed by monitoring GFP levels expressed by the prey strain, obviates the need for laborious quantitative competition assays as an initial screen of candidates. To test a candidate effector in the surrogate platform, one simply needs to amplify the DNA sequence of the candidate E/I pair in question (or order the cassette from a variety of commercial vendors), introduce it into the surrogate platform strain (and into its T6SS − negative control derivative), and employ it in bacterial competition (either quantitative or qualitative) against the surrogate platform's parental strain that lacks immunity against the exogenous effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T6SS1 is active under warm marine-like conditions (3% NaCl, 30°C), whereas T6SS2 is active under low salinity and low temperature (1% NaCl, 23°C) ( Salomon et al, 2013 ). Recent studies have indicated that T6SSs are tightly regulated in pathogenic bacteria, for example, Vibrio cholerae , Pseudomonas aeruginosa , and V. parahaemolyticus , and induced by external conditions and cues such as quorum sensing, salinity, temperature, mucin, chitin, surface sensing, and cell membrane damage ( Ben-Yaakov and Salomon, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…QS has been widely identified in Gramnegative and Gram-positive bacteria and is fundamental for cell-to-cell communication (Juhas et al, 2005;Kai and Bassler, 2016). Hundreds of traits can be regulated via QS in both pathogenic and environmental bacteria, such as EPS synthesis, biofilm formation, cell colonization, bioluminescence and the secretion of virulence factors (Goo et al, 2015;Ben-Yaakov and Salomon, 2019). QS can also regulate metabolic processes in some bacteria, such as sugar and phosphate metabolism, as well as secondary metabolites (Goo et al, 2015;Certner and Vollmer, 2018;Ha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%